2022
DOI: 10.1021/acs.est.1c04299
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Alkylated and Unsubstituted Polycyclic Aromatic Hydrocarbons in Air in Urban and Semi-Urban Areas in Toronto, Canada

Abstract: 22 alkylated polycyclic aromatic hydrocarbons (alk-PAHs) were characterized in ambient air individually for the first time in urban and semi-urban locations in Toronto, Canada. Five unsubstituted PAHs were included for comparison. Results from the measurements were used to estimate benzo­[a]­pyrene equivalent toxicity (BaPeq) of individual compounds in order to investigate the significance of a single compound in contributing to the overall toxic equivalency (TEQ) of air mixtures. To determine which compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…36 Four of these compounds are alkylated derivatives and are not classied by the EPA as hazardous. Alkylated PAHs have higher abundance than their non-alkylated forms in many environmental media, including crude oil, 35 ambient air, 37,38 cigarette smoke 36 and plant and animal tissue samples. 39 A recent study in sh found that 3 ring alkylated PAHs were more persistent, bioaccumulated, and toxic than their parent compounds.…”
Section: Detecting Pahs Exposure Using Wristbandsmentioning
confidence: 99%
“…36 Four of these compounds are alkylated derivatives and are not classied by the EPA as hazardous. Alkylated PAHs have higher abundance than their non-alkylated forms in many environmental media, including crude oil, 35 ambient air, 37,38 cigarette smoke 36 and plant and animal tissue samples. 39 A recent study in sh found that 3 ring alkylated PAHs were more persistent, bioaccumulated, and toxic than their parent compounds.…”
Section: Detecting Pahs Exposure Using Wristbandsmentioning
confidence: 99%
“…1-ethylpyrene is only one of the alkylated analogs of pyrene; other AlkPAHs like 4,5-dimethylpyrene and 1-propylpyrene have been reported in the atmosphere. 15,17,18 It is worth noting that the levels of AlkPAHs in the atmosphere surpass those of the original PAHs, and each PAH can have multiple alkylated analogs. 15,17,18 Based on the ndings of this study, it is evident that AlkPAHs exhibit a higher reactivity with ozone compared to PAHs and produce a greater variety of OPAHs.…”
Section: Oxidation Productsmentioning
confidence: 99%
“…13,14 Notably, recent research has reported higher AlkPAH levels than PAH levels at several Canadian locations. [15][16][17][18] Given the growing evidence of AlkPAHs' prevalence in the atmosphere and their potential health risks, investigating their transformations in the atmosphere is imperative. PACs undergo photolysis upon ultraviolet exposure and oxidation through reactions with gas-phase oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The cancer risks of PAHs and nitro-PAHs are often estimated using the equivalents of benzo(a)pyrene (BaP eq ), one of the most potent PAHs with known carcinogenic characteristics. The toxic equivalent factor (TEF) for BaP is set to 1, and other PAHs and nitro-PAHs are assigned a TEF value by comparing their relative toxicity to that of BaP (ATSDR, 2022;Samburova et al, 2017;Moradi et al, 2022). For PAHs, dibenzo[a,h]anthracene has the highest TEF of 2.4, followed by BaP, benzo[e]pyrene and dibenzo[a,e]pyrene, with a TEF of 1.0 (ATSDR, 2022;Samburova et al, 2017).…”
Section: Non-polar Organic Compoundsmentioning
confidence: 99%